(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
This article presents the results of the research about the relationship between the fashion education in Rio de Janeiro today and the constitution of the Schools of Arts and Crafts in the state, taking into account the position and economic and cultural relevance that the state occupied as the country’s capital from 1763 to 1960. For this, the research carried out a survey of undergraduate, technological, technical, continuing education and free courses associated with the world of fashion currently in the state and evaluated the results, relating it to an investigation on the installation of the Schools of Arts and Crafts in Rio de Janeiro in the 19th century, aiming to analyze how notions and values present in the installation of these institutions impact manual and artistic production associated with fashion today.